Penerapan Social Enterpreneurship dalam Memberdayakan Masyarakat Miskin Perkotaan - Zaili Rusli; Chalid Sahuri; Dadang Mashur; Mayarni ' (Jurnal Kebijakan Publik, 2011)
Pekanbaru is one city in Indonesia that have evolved so rapidly, especially in the economic field.Developments led the city witnessed a social change and urban development that is high enough. The impactof social changes that took place between the other is the high level of poverty. To overcome the problem ofpoverty is one of them with the development of social entrepreneurship is developing social entrepreneurs byway of changing behavior and understanding or awareness of those around him. Where has the transformativepower of social entrepreneurs with new ideas to exploit and create opportunities in the face of big problems,who was tireless vision to successfully deploy an idea he had. This study aims to determine and analyze thepicture of the factors that affect the application of social entrepreneurship in empowering the poor throughprograms UEK - SP in the city of Pekanbaru.